Motion-based design approach for a novel variable friction cladding connection used in wind hazard mitigation. (15th February 2019) - Gong, Yongqiang; Cao, Liang; Laflamme, Simon; Ricles, James; Quiel, Spencer; Taylor, Douglas
Highlights: Novel variable friction cladding connection applied to wind mitigation. Analytical responses derived on structure-cladding system. Motion-based design approach developed for wind mitigation. Device and design methodology demonstrated numerically. Abstract: Cladding systems typically serve architectural purposes and protect occupants against the external environment. It is possible to leverage these systems to enhance structural resiliency. A common application is the use of blast resistant panels for enhanced protection against man-made hazards, whereas energy is dissipated through sacrificial elements. However, because these protection systems are passive, their mitigation capabilities are bandwidth limited, therefore targeting single types of hazards. The authors have recently proposed a novel variable friction cladding connection (VFCC), which enables the leveraging of cladding inertia for mitigating blast, wind, and seismic hazards. The variation in the friction force is generated by an actuator applying pressure onto sliding friction plates via a toggle system. Previous work has characterized the dynamic behavior of a VFCC prototype, and established design procedures for blast mitigation applications. Here, work is extended for applications to wind mitigation. An analytical model is developed to characterize the dynamic behavior of the VFCC for wind-induced vibrations. A motion-based design framework is developed to enable an holistic integration of the device within the structural design phase. Numerical simulations are conducted on a 24-story building example to demonstrate the motion-based design methodology. Results show that the semi-active cladding system provides significant reduction in the wind-induced inter-story drift and floor acceleration, therefore demonstrating the promise of the VFCC for field applications.